IMPLEMENTASI KEBIJAKAN PENDAFTARAN TANAH PADA KANTOR PERTANAHAN KABUPATEN DONGGALA PROVINSI SULAWESI TENGAH - Madjid, Herman (Katalogis, 2016)
This Research Target is know and analyse The Policy Implementation Of Land Registry At Office Land Donggala Regency Central Sulawesi Province. this Research Type is research qualitative with the informan selected by the four of people. Data collecting use the technique interview and documentation. Technique analyse the data used by that is (1) Data collecting (2) Data Discount (3) Data Presentation (4) Verification (5) Conclusion. The researcher Theory used in this is Van of metre and Horn Van in (Subarsono, 2005), measuring policy implementation by: (1) standard and Target (2) Resource (3) Communications (4) Executor (5) social Condition and ( 6) Disposition. The result of research and analysis a researcher is hence concluded the implementation of policy land registry not yet walked better, with the the following detail: (1) Implementation policy of]land registry in Office Land Donggala Regency seen from factor of standard and policy target not yet walked better, seen from time duration still in land registry become the certificate, so that society feel saturated in conducting land registry and visit upon the Office of Land Donggala Regency (2) Implementation of policy land registry in Office Land of Donggala Regency seen from Resource factor not yet walked better this matter is seen from medium and prasarana not yet adequate and also sum up the officer which still office Land Donggala Regency. (3) Implementation of policy land registry in Office Land Donggala Regency seen from factor comunication, characteristic, political and economic social condition and also disposition factor not yet walked better, this matter is seen from facility which disedikan not yet adequate is and also supported by result of interview with the informan conducted by a field telling not yet walked better